COMPARISON OF ECONOMIC EFFECTIVENESS BETWEEN TROLLEY AND BUS OPERATION PROCESS ACCORDING TO ECOLOGICAL FACTOR - Yu. O. Glushkova; A. V. Pahomova; A. R. Asoyan (Вестник СибАДИ, 2018)
Introduction. The article presents the results of the comprehensive comparative study of economic efficiency of the rolling stock on urban transport, such as trolley with dynamic charging and diesel bus, in order to solve a new problem for a large city of identifying more profitable vehicle in terms of economic, environmental and time factors.Materials and methods. Such methods as index, comparison methods and methods of analytical calculations and dynamic series analysis are applied in the research.Results. As a result, the algorithm of the transport mode choosing and step by step instructions of the comparison, wherein the integrated approach to the assessment of performance, was established. In addition, the necessity of supposed recommendations’ application on implementation of comparison process of technical, operational and economic indicators, which take into account the revealed advantages and shortcomings of the existing types of the rolling stock was proved on the basis of the hybrid trolley and bus on diesel fuel.Discussion and conclusions. The statistical study of dynamics’ series of environmentally friendly urban modes of passenger transport by the following factors as the operational length of trolley and tram routes, volume of passenger traffic on public transport in the Russian Federation and also in Volga Federal District and its regions. The model of step-by-step process of calculation of transportations’ prime cost by alternative modes of transport is offered on the example of trolley with dynamic recharging and city bus.